A series of red iridium(iii) complexes using flexible dithiocarbamate derivatives as ancillary ligands for highly efficient phosphorescent OLEDs. (27th March 2019) - Lu, Guang-Zhao; Wu, Ruixia; Liu, Liang; Zhou, Liang; Zheng, You-Xuan; Zhang, Wen-Wei; Zuo, Jing-Lin; Zhang, Hongjie
Abstract : Five red iridium(iii ) complexes with dithiocarbamate ligands were investigated, and their OLEDs exhibit an EQEmax of 20.69% with low efficiency roll-off. Abstract : Five red cyclometalated iridium(iii ) complexes containing the unique four-membered ring Ir–S–C–S backbone with different dithiocarbamate derivatives as ancillary ligands and 1-(4-(trifluoromethyl)phenyl)isoquinoline (4tfmpiq) as the main ligand were synthesized at room temperature within ten minutes. The emission color ( λ peak = 607–619 nm) and photoluminescence quantum efficiency (PLQY) ( Φ P = 36.6–63.0%) can be effectively tuned by introducing different electron – donating substituents such as diisopropylamine (dipdtc), diphenylamine (dpdtc), bis(4-( tert -butyl)phenyl)amine ( t Budpdtc), carbazole (Czdtc) and 3, 6-di- tert -butyl-9 H -carbazole ( t BuCzdtc) into the dithiocarbamate ancillary ligands. Employing (4tfmpiq)2 Ir(dipdtc) as the emitter, the organic light emitting diodes (OLEDs) with double emitting layers exhibit good performances with a maximum current efficiency ( η c, max ) of 18.67 cd A −1, an EQEmax of 20.69% and low efficiency roll-off with an EQE of 18.11% at the practical luminance of 1000 cd m −2 . The Commision Internationale de L'Eclairage coordinates of (0.660, 0.337) are quite close to the National Television System Comittee (NTSC) standard red emission. These results demonstrate that by introducing different electron – donating substituents into the dithiocarbamate ligands, the diversity of the S–C–S ligands is greatly enriched for red Ir(iii ) complexes and the corresponding OLEDs.